Interleukin-17A: The Key Cytokine in Neurodegenerative Diseases - Chen, Junjue; Liu, Xiaohong; Zhong, Yisheng (Frontiers in Aging Neuroscience, 2020)
Neurodegenerative diseases are characterized by the loss of neurons and/or myelin sheath, which deteriorate over time and cause dysfunction. Interleukin 17A is the signature cytokine of a subset of CD4+ helper T cells known as Th17 cells, and the IL-17 cytokine family contains six cytokines and five receptors. Recently, several studies have suggested a pivotal role for the IL-17A cytokine family in human inflammatory or autoimmune diseases and neurodegenerative diseases, including psoriasis, rheumatoid arthritis, Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, amyotrophic lateral sclerosis and glaucoma. Studies in recent years have shown that the mechanism of action of IL-17A is more subtle than simply causing inflammation. Although the specific mechanism of IL-17A in neurodegenerative diseases is still controversial, it is generally accepted now that IL-17A causes diseases by activating glial cells. In this review, we will focus on the function of IL-17A, in particular the proposed roles of IL-17A, in the pathogenesis of neurodegenerative diseases.